EXPLORING THE VALUES OF FAITHA MORALITY TO SHAPE STUDENTS WITH NOBLE CHARACTER - Fadil Maulana Al Karomy; Muhammad Sa'roni; M. Mahbubi (International Journal of Multidisciplinary Reseach, 2025)
This study aims to explore the implementation of aqidah (faith) and akhlak (morality) values in the learning process at SMP Nuruljadid, Paiton, Probolinggo, and their impact on the character formation of ninth-grade students. Using a qualitative descriptive approach, data were collected through observations, interviews with teachers and students, as well as documentation related to the curriculum and teaching materials. The findings indicate that the teaching of aqidah and akhlak at SMP Nuruljadid is carried out using a contextual approach that emphasizes the application of religious values in everyday life. Teachers deliver the material through lectures, discussions, and direct interactions that engage students in understanding and applying these values. Interviews with teachers revealed challenges in delivering aqidah and akhlak content, particularly due to the influence of social media, which often contradicts religious values. On the other hand, students felt that this learning had a positive impact on their character development, although some admitted to facing difficulties in consistently applying the values outside of the school environment. The study concludes that the learning of aqidah and akhlak at SMP Nuruljadid significantly contributes to the formation of students’ noble character, despite ongoing external challenges. This research provides insights for the development of more effective Islamic religious education in other schools.